Fate of abstracts presented at the annual meetings of the American association of clinical anatomists. Issue 2 (27th January 2017) - Furness, Hugh; Miller, George W.; Putt, Oliver; Lewis, Thomas L.
Abstract : A recent study examined the rate of full‐length research paper publication following abstract presentation at the British association of clinical anatomists (BACA) annual meetings. The accepted standard for research dissemination is peer‐reviewed publication following presentation at a national or international meeting. The study objectives were quantitative assessment of the abstracts presented at the American Association of Clinical Anatomists' (AACA) annual meetings with regards to the rate of subsequent full‐length publication and comparison to BACA publication rates. All abstracts presented at the AACA annual meetings between 2003 and 2010 were analysed. MEDLINE was searched to identify peer‐reviewed publications arising from each presented abstract. In total, 1, 120 abstracts were presented with 22.9% ( n = 257) subsequently published as full‐length research papers. The mean number of abstracts presented each year was 140.0 ± 35.9. The median time to publication was 16 months. Chi‐squared analysis showed the publication rate of abstracts presented at AACA (22.9%) was not statistically significantly different to BACA (20.4%) ( P = 0.09). A total of 11.3% ( n = 29) of the articles were published as full‐length research articles before presentation as an abstract at an AACA meeting compared to 5.4% of abstracts presented at a BACA meeting. These rates are lower but comparable to those of surgical specialty meetings. Further work should try to identify any concerning reasons for the reduced rate of abstract publication in anatomical research. Clin. Anat. 30:140–144, 2017. © 2017 Wiley Periodicals, Inc.